UPAYA INDUSTRI PERKERETAAPIAN INDONESIA DALAM MENGEKSPOR GERBONG KERETA API KE BANGLADESH 2016-2019 - Novi Razi; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research describes the efforts of the Indonesian railway industry in exporting train carriage to Bangladesh in 2016-2019. The efforts made by the Indonesian government in the Jokowi Dodo government which is considered very aggressive towards Bangladesh in terms of exporting the goods. Indonesia government has done good efforts to increase the value of Indonesian exports. This research uses the perspective of Liberalism with the concept of International Cooperation from the perspective of Liberalism. The theory used in this research is the theory of Export-Import according to David Ricardo with the level of analysis of the Nation-State. This result uses qualitative methods with data collection techniques in the form of written text journals, books, official websites, websites, and media. The result of this research is that PT.INKA succeeded in increasing the value of exports trough bidding, providing carriages, providing policies and conducting events to introduce products from PT.INKA to Bangladesh Keywords : PT.INKA, Indonesian Exporter Efforts, Bangladesh